Scoping the Sharing Economy: Origins, Definitions, Impact and Regulatory Issues - Cristiano Codagnone; Bertin Martens (European Commission, Joint Research Centre (JRC), 2016)
This report selectively draws on the systematic review of a large set of data sources, which is presented elsewhere, and comprises 430 secondary sources (Codagnone, 2016). The report also provides a critical overview of key analytical, empirical, and normative dimensions of the `sharing economy'. It reviews both the rhetorical and controversial debates currently surrounding the topics and the available empirical evidence in order to sharpen our understanding of relevant policy and regulatory issues. The broad umbrella term 'sharing economy' is critically assessed and a typology developed that identifies the commercial 'peer to peer' sharing economy as the main focus of both controversies and policy-relevant issues. Empirical evidence of the benefits and costs of the sharing economy and its implications for sustainability and employment is very limited and inconclusive, particularly as regards the European landscape. This critical review, hence, shows that, as yet, there are no unambiguous answers to some of the fundamental questions about the `sharing economy'. The available research is too limited and patchy to give us a comprehensive and coherent picture. This report's main contribution is to clear some of the conceptual and empirical fog around the `sharing economy' and to identify where possible answers might be found in the future. It is suggested that the definition of sharing platforms should focus on P2P activities, as most of the policy concerns are found there. These include regulatory and consumer protection issues resulting from the informal production of services, potentially unfair competition with formal B2C service providers, and questions related to dominance and market power of P2P platform operators as commercial businesses.
Keywords: F15; 330; multi-sided markets; collaborative economy; sharing economy; peer-to-peer markets